Placing Sin in Karl Rahner’s Theology - Fritz, Peter Joseph (Irish theological quarterly, 2015)
Karl Rahner is seldom viewed as a theologian of sin: precisely the contrary. A recent book by Emmie Ho-Tsui (published in Austria, 2011) reopens the question of sin’s place in Rahner’s works. This article reports on Ho-Tsui’s book and carries her inquiry forward, with special focus on Rahner’s studies on penance and with a renewed look at his idea of the fundamental option. Rahner recovers the ancient idea of penance as reconciliation with the church, implying that sin can be best understood in terms of the break from and return to ecclesial communion. Rahner’s insistence that human persons can pronounce a definitive ‘no’ to God affirms sin’s reality, thus the need for ecclesial reconciliation. Taken together, his penance studies and thoughts on the fundamental option comprise an agenda for articulating the radical mercy that the church is called to—but often does not—enact.